Comparison of thyroid gland involvement in contrast enhanced computed tomography of the neck and histopathology and the necessity of thyroidectomy in patients with laryngeal and hypo pharyngeal cancer - Kathar M., Mohamed Abdul; Michael, Rajiv; Shyam, Aparna (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: The aim of this study is to assess the thyroid gland involvement in the preoperative contrast enhanced computed tomography (CECT) of neck with histopathology (HPE) in determining the indications for ipsilateral thyroidectomy in patients undergoing total laryngectomy in laryngeal and hypopharyngeal cancers. Methods: Forty patients diagnosed clinically with stage 3 laryngeal and hypopharyngeal cancer were subjected to CECT of neck. Patients with cartilage erosion and extra laryngeal spread on CECT (T3, T4a) were routinely taken for total laryngectomy, partial pharyngectomy and hemi thyroidectomy. Specimens were sent for histopathological analysis and which was compared with preoperative CECT scan. Results: Of the forty cases, only four patients had thyroid gland involvement in CECT scan and 2 of the 40 had thyroid gland involvement in histopathology. Of the four patients where the CT scan which showed infiltration of the thyroid gland, none had thyroid gland involvement in histopathology. In two patients where thyroid gland was involved in histopathology, CT scan failed to pick up the thyroid gland involvement. Those two patients with histologically proven thyroid gland involvement identify as transglottic malignancy with cartilage erosion and extra laryngeal spread. Conclusions: Our study concludes that an ipsilateral hemi-thyroidectomy is probably still indicated in transglottic cancer with cartilage invasion and/or extra laryngeal spread.